The evolution of the Theory of Human Care to the Science of Unit Care (Research, Society and Development, 2020)
The Theory of Human Care or Unit Care Science is used worldwide and is constantly evolving. Over the years, along with the evolution of Theory, there has been an evolution of paradigms, moving from Caritatives Factors to Elements of the Clinical Caritas Process and recently, Elements of the Clinical Caritas-Veritas Process. Objective: To present the evolution of the Theory of Human Care to the Science of Unitary Care and the resonances on the Elements of the Clinical Caritas-Veritas Process. Method: Theoretical reflection on the conceptual aspects and principles of the Theory of Human Care and the evolution / change of paradigms for the Science of Unitary Care. Results: A special emphasis is placed on the Elements of the Clinical Caritas Process from the Caritas-Veritas perspective. These core aspects of the concepts are developed in the philosophical and ethical foundation of the unitary care science body. Final consideration: It is believed that this manuscript may serve as a primary disciplinary scheme for the professional practice of nurses when using the Science of Unitary Care.